Assessing the diagnostic validity of a blind register - Crewe, Julie; Morgan, W.; Morlet, Nigel; Spilsbury, Katrina; Mukhtar, Syed Aqif; Clark, Antony; Ng, Jonathon; Crowley, Margaret; Semmens, James (Wiley-Blackwell Publishing Asia, 2011)
Background:  To validate the accuracy of clinical ophthalmic information held on the West Australian blind register. Design:  Community-based cross-sectional study. Participants:  Legally blind or severely vision-impaired people were selected randomly from the Association for the Blind of Western Australia register. Methods:  Individuals were reviewed by one of two consultant ophthalmologists. Main Outcome Measures:  The positive predictive value (ppv), sensitivity and specificity for legal blindness status and diagnostic causes of vision loss were calculated using data extracted from the Association for the Blind of Western Australia blind register. Results:  273 blind or near blind people were reviewed from the register total of 4271 individuals. There were more women (57%) than men, median age 81 years. For legal blindness status the ppv was 0.88 (95% confidence interval [CI] 0.82–0.92), sensitivity 0.75 (95% CI 0.74–0.84) and specificity 0.6 (95% CI 0.46–0.73). The ppv for the diagnostic causes of blindness were: age-related macular degeneration = 0.95 (95% CI 0.91–0.97), retinitis pigmentosa ppv = 1 (95% CI 0.81–1.0), diabetic retinopathy ppv = 0.9 (95% CI 0.57–0.99), optic neuropathies ppv = 0.77 (95% CI 0.51–0.92) and glaucoma ppv = 0.87 (95% CI 0.7–0.96). Forty individuals (15%) had treatable conditions contributing to their vision loss. Conclusions:  The blind register diagnoses and legal blindness status are of high accuracy. This information allows useful linkages to other databases for studies of blindness interactions. A regular updating mechanism would improve the future accuracy of this valuable regional asset. The presence of untreated cataract suggests that regular follow up and appropriate treatment may help optimize vision in blind patients.